The Impact of English Cartoons on Children’s English Language Development: A Case Study - Salah Elfeitouri, Nisreen (Scientific Journal of University of Benghazi, 2025)
Cartoons can teach children a vast amount of information and valuable life lessons in an entertaining and engaging manner. Cartoons can also help children acquire various skills, like collaboration, negotiating, critical thinking, and problem-solving. In addition, cartoon-viewing has been increasingly linked with children’s language development and improvement. Accordingly, this study examined the impact of watching English cartoons on children’s English language acquisition in the Libyan setting. Case study research was conducted, which involved three years of direct observation of a two-year-old Libyan girl. The data analysis and results revealed that a purposeful and consistent approach to watching English cartoons can lead to remarkable English language learning outcomes. Specifically, the child in this study demonstrated notable English language development across various areas, including vocabulary, grammar, sentence structure, pronunciation, comprehension, production, and emotional expression. The findings of this study shed light on the benefits of following a systematic approach to using English language media-based content as an innovative and motivating method for English language teaching and learning in the Libyan home environment and Libyan English language learning classroom.